2015
DOI: 10.1158/1055-9965.epi-14-0262
|View full text |Cite
|
Sign up to set email alerts
|

Enterolignan-Producing Phenotypes Are Associated with Increased Gut Microbial Diversity and Altered Composition in Premenopausal Women in the United States

Abstract: Background Lignans in plant foods are metabolized by gut bacteria to the enterolignans, enterodiol (END) and enterolactone (ENL). Enterolignans have biologic activities important to the prevention of cancer and chronic diseases. We examined the composition of the gut microbial community (GMC) as a contributor to human enterolignan exposure. Methods We evaluated the association between the GMC in stool, urinary enterolignan excretion, and diet from a 3-day food record in 115 premenopausal (ages 40–45 y) women… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 91 publications
(106 reference statements)
5
58
0
Order By: Relevance
“…Accordingly, we previously reported that increased excretion of ENL is associated with composition and diversity of the gut microbial community. 46 Unlike plant lignan intakes, mean excretion of ENL (4.6 µmol on WG diet and 3.0 µmol on RG diet) and END (0.82 µmol on WG diet and 0.41 µmol on RG diet) of participants in our study was consistent with what has been reported previously, 4750 although not as high as END and ENL levels obtained (9–12 µmol/24h) after ingestion of a single dose of SDG (1.3 µmol/kg body weight). 8 We did not observe a statistically significant linear association between ENL and plant lignan intakes.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we previously reported that increased excretion of ENL is associated with composition and diversity of the gut microbial community. 46 Unlike plant lignan intakes, mean excretion of ENL (4.6 µmol on WG diet and 3.0 µmol on RG diet) and END (0.82 µmol on WG diet and 0.41 µmol on RG diet) of participants in our study was consistent with what has been reported previously, 4750 although not as high as END and ENL levels obtained (9–12 µmol/24h) after ingestion of a single dose of SDG (1.3 µmol/kg body weight). 8 We did not observe a statistically significant linear association between ENL and plant lignan intakes.…”
Section: Discussionmentioning
confidence: 99%
“…4,13,[16][17][18][19][20][21][22] Recently, various publications suggest that Streptobacillus species might be far more common and distributed in the environment or as commensal microbiota than previously thought. 32,37,[59][60][61][62][63] It could recently be shown that the natural reservoir for the very rare cases of human S. hongkongensis infection known to date is indeed the human oropharynx à and presumably not an unidentified animal or environmental reservoir. 49 Despite a certain amount of annually published case reports, most of which have solely used 16S rRNA sequencing alone for definite diagnosis, there has not been much progress in the diagnosis of acute clinical cases of RBF in the last decades.…”
Section: Discussionmentioning
confidence: 99%
“…1). 62,63 This fuels the assumption that Streptobacillus species are far more distributed in the environment aside from their natural hosts than previously thought. Contrarily, former Streptobacillus-like organisms from fish 55 and guinea pigs [64][65][66][67] are even more distantly related to classical Streptobacillus species and indeed represent novel genera, that have been recently described.…”
Section: Host Spectrummentioning
confidence: 99%
“…The equol production phenotype was transferrable to germ-free rats: rats produced equol when they received a fecal microbiota transplant from individuals with high equol production, but not when they received a transplant from individuals with low equol production. There is a lack of data on microbial pathways for isoflavone and lignan metabolite production, but one recent study reported a positive association between gut microbiota diversity, based on 16S rRNA analysis, and enterolignan production in 115 premenopausal U.S. women[11]. …”
Section: Integrated Approaches To Functional Understanding Of the Intmentioning
confidence: 99%
“…On an individual level, dietary composition contributes, at least in part, to shaping the gut microbiota through the delivery of energy for microbial growth[68]. In turn, gut microbiota influence the production of health-related metabolites from dietary components[9, 10], with the potential for personal variability in metabolite production based on differences in gut microbiota[11, 12]. A growing literature supports a role for gut microbiota in the development and progression of metabolic and cardiovascular disease risk[1316], including type 2 diabetes[1719], obesity[2022], insulin resistance[23], inflammation[24], atherosclerosis[12, 25], hypertension[26, 27], dyslipidemia[28], and cardiovascular disease events[29, 30].…”
Section: Introductionmentioning
confidence: 99%